Curriculating from the Black Archive –Marginality as Novelty - Kumalo, Siseko Hudson (Critical Studies in Teaching and Learning, 2023)
The Black Archiveis constitutive of works of literato such as JT Jabavu, Nontsizi Mgqwetho, the artist Gerard Bhengu, and musicianslikeBusi Mhlongo. This collective resource, which should play a crucialrole incurriculating, compels us to consider two questions when rethinking Philosophy curricula:  First, pedagogically, how does the epistemic access that the Black Archive afford sour context facilitate justice? Second, and importantly, how does it help us in achieving justice? I, here, answer these questions in three moves. First, I consider certain key propositions; namely that decolonisation facilitates epistemic access, and that epistemic access in turn facilitates justice (historical, epistemic, and social). Second, I demonstrate how these propositions require the Black Archive (in South Africa) in order to be held as valid. I demonstrate this claiminPhilosophy using Dumile Feni’s African Guernica, and in Curriculum Studies, through analysing W. W. Gqoba’s Ingxoxo Enkulu Ngem fundo. I conclude by prescriptivel you tlining uses for/of the Black Archive, guarding against misappropriations that derail justice as I treat it, safe guarding this corpus from epistemic arrogance that maintains that knowledge is valid only in so far as it  is developed by white scholars.